Effects of hedonic shopping motivations and gender differences on compulsive online buyers - Wang, Xuhui; Ali, Fayaz; Tauni, Muhammad Zubair; Zhang, Qilin; Ahsan, Tanveer (Journal of marketing theory and practice, 2022)
Online shopping addiction has become a worsening problem in China for males and females. Based on 904 shoppers, this study examines the relationship between hedonic shopping motivations and compulsive online buying and investigates gender differences using gender theories. This study finds that different hedonic motivations contribute to compulsive online buying. Gratification seeking and idea shopping are key motivations for compulsive online buyers (females are mostly gratification seekers, while males are mostly information seekers). Conversely, value and role-play shopping reduce compulsive online buying, with a stronger effect on females; however, role-play shopping was unrelated to compulsive online buying for males.